A comprehensive review of measurements and data analysis of laminar burning velocities for various fuel+air mixtures. (September 2018) - Konnov, Alexander A.; Mohammad, Akram; Kishore, Velamati Ratna; Kim, Nam Il; Prathap, Chockalingam; Kumar, Sudarshan
Abstract: Accurate measurement and prediction of laminar burning velocity is important for characterization of premixed combustion properties of a fuel, development and validation of new kinetic models, and calibration of turbulent combustion models. Understanding the variation of laminar burning velocity with thermodynamic conditions is important from the perspective of practical applications in industrial furnaces, gas turbine combustors and rocket engines as operating temperatures and pressures are significantly higher than ambient conditions. With this perspective, a brief review of spherical flame propagation method, counterflow/stagnation burner method, heat-flux method, annular stepwise method, externally heated diverging channel method, and Bunsen method is presented. A direct comparison of power exponents for temperature (α) and pressure (β) obtained from different experiments and derived from various kinetic mechanisms is reported to provide an independent tool for detailed validation of kinetic schemes. Accurate prediction of laminar burning velocities at higher temperatures and pressures for individual fuels will help in closer scrutiny of the existing experimental data for various uncertainties due to inherent challenges in individual measurement techniques. Laminar burning velocity data for hydrogen (H2 ), gaseous alkane fuels (methane, ethane, propane, n-butane, n-pentane), liquid alkane fuels (n-heptane, isooctane, n-decane), alcohols (CH3 OH, C2 H5 OH, n-propanol, n-butanol, n-pentanol) and di-methyl ether (DME) are obtained from literature of last three decades for a wide range of pressures (1–10 bar), temperatures (300–700 K), equivalence ratios and mixture dilutions. The available experimental and numerical data for H2 and methane fuels compares well for various pressures and temperatures. However, more experimental and kinetic model development studies are required for other fuels. Comparison of laminar burning velocity data obtained from different measurement techniques at higher initial pressures and temperatures showed significant deviations for all fuels. This suggests to conduct focused measurements at elevated pressure and temperature conditions for different fuels to enable the development of accurate kinetic models for wider range of mixtures and thermodynamic conditions.